Complete abatement of the antibiotic ciprofloxacin from water using a visible-light-active nanostructured photoanode - Changanaqui, Katherina (2024)
The wide use of the fluoroquinolone antibiotic ciprofloxacin (CIP), combined with its limited removal in wastewater treatment plants, results in a dangerous accumulation in natural water. Here, the complete degradation of CIP by photoelectrocatalysis (PEC), using an FTO/ZnO/TiO2/Ag2Se photoanode that is responsive to blue light, has been investigated. A slow antibiotic concentration decay was found in 0.050 M Na2SO4 under the oxidizing action of holes and radical dotOH photogenerated at the anode surface. The degradation was strongly enhanced in 0.070 M NaCl due to mediated oxidation by electrogenerated active chlorine. The latter process became faster at pH 7.0, with total abatement of CIP at concentrations below 2.5 mg L−1 operating at a bias potential of +0.8 V. The performance was enhanced when increasing the anodic potential and decreasing the initial drug content. The use of solar radiation from a simulator was also beneficial, owing to the greater lamp power. In contrast, the electrochemical oxidation in the dark yielded a poor removal, thus confirming the critical role of oxidants formed under light irradiation. The generation of holes and radical dotOH was confirmed from tests with specific scavengers like ammonium oxalate and tert-butanol, respectively. The prolonged usage of the photoanode affected its performance due to poisoning of its active centers by degradation by-products, although a good PEC reproducibility was obtained upon surface cleaning.